Improving Students' Al-Qur'an Memoration In The Al-Qur'an Hadith Subject Through The Takrir Method in XII Grade Student at Madrasah Aliyah Laboratorium, Jambi - Siti Aisyah (Journal of Curriculum and Pedagogic Studies (JCPS), 2023)
The takrir method serves as a means for information entering short-term memory to transfer directly into long-term memory, achieved through repetition (rehearsal or takrir). This research aimed to enhance students' memorization of the al-qur'an in al-qur'an hadith subjects. The research employed a classroom action research approach involving 20 students of XII IPS at Madrasah Aliyah Labor Jambi. It encompassed 3 stages: pre-cycle, cycle 1, and cycle 2. The research findings indicated improved student learning outcomes: Initially, only 5 out of 20 students (25%) completed the task. After implementing the assessment method in cycle I, 15 students (75%) successfully completed it. In cycle II, following further improvements, 19 students (95%) successfully completed it, demonstrating a significant enhancement from the previous state.